Study of Ultrasonic Velocity in Ternary Liquid Mixtures Using Surface Tension Relations - Kumar Sahu, Deo (Asian Journal of Chemistry, 2010)
Surface tension has been evaluated for the ternary liquid mixtures at 298.15 K. These values have been employed in the prediction of ultrasonic velocity using Auerbach relation. A good agreement between experimental and evaluated values has been reported.